2004
DOI: 10.1016/j.jalgebra.2003.12.009
|View full text |Cite
|
Sign up to set email alerts
|

On presentations of surface braid groups

Abstract: We give presentations of braid groups and pure braid groups on surfaces and we show some properties of surface pure braid groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
123
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(128 citation statements)
references
References 18 publications
0
123
0
2
Order By: Relevance
“…it twists only i-th and j-th strands. Each generator in the set S \ S ′ naturally corresponds to one of the generators of π 1 (Σ g , z i ) described above, see [4].…”
Section: B Proof Of Theorem 2 Let G >mentioning
confidence: 99%
See 1 more Smart Citation
“…it twists only i-th and j-th strands. Each generator in the set S \ S ′ naturally corresponds to one of the generators of π 1 (Σ g , z i ) described above, see [4].…”
Section: B Proof Of Theorem 2 Let G >mentioning
confidence: 99%
“…Denote this set by QCal g . It is infinite and it does not contain non-trivial homomorphisms, since every homomorphism on B 2 (Σ g ) must be trivial on B 2 , see [4].…”
Section: F2mentioning
confidence: 99%
“…The study of braid groups on surfaces has been revived recently. González-Meneses [2001] found new presentations of the braid groups on surfaces, and the authors of [Bellingeri 2004;Bellingeri and Godelle 2007] found positive presentations of the braid groups B n,k ( ) for all surfaces , with or without boundary. Here, we are interested in braid groups on surfaces with nonempty boundary and will use Bellingeri's presentations.…”
Section: Introductionmentioning
confidence: 99%
“…Then there are continuous maps i : q → and j : → q that are homotopy inverses each other. The induced mapsī : B n+q,k ( ) → B n,k ( ) andj : B n,k ( ) → B n+q,k ( ) on configuration spaces are also homotopy inverses each other and induce isomorphismsī * andj * on fundamental groups [Bellingeri 2004;Paris and Rolfsen 1999]. Therefore we may assume = (g, 1) by treating all but one boundary component as a puncture whenever we deal with a surface with nonempty boundary.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, for a given surface Σ, one can extract geometric information from its braid group as follows. The proof is obvious by the group presentation for B n (Σ), see [5], and we omit the proof.…”
Section: Theorem 24 [6]mentioning
confidence: 99%